2016
DOI: 10.1098/rspb.2016.0163
|View full text |Cite
|
Sign up to set email alerts
|

Population-dependent effects of ocean acidification

Abstract: Elevated carbon dioxide levels and the resultant ocean acidification (OA) are changing the abiotic conditions of the oceans at a greater rate than ever before and placing pressure on marine species. Understanding the response of marine fauna to this change is critical for understanding the effects of OA. Population-level variation in OA tolerance is highly relevant and important in the determination of ecosystem resilience and persistence, but has received little focus to date. In this study, whether OA has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…Tolerances to elevated pCO22 vary among marine invertebrate species, as do tolerances to changes in salinity (e.g. Sokolova et al 2016;Wood et al 2016). Little, however, is known about their combined effects and our current understanding in filter feeders is limited to just a few studies where it has been shown that these factors influence the survival, energy metabolism and osmoregulatory capacity as well as weaken shells.…”
Section: Such Species Include Economically Important Filter Feeders Smentioning
confidence: 99%
“…Tolerances to elevated pCO22 vary among marine invertebrate species, as do tolerances to changes in salinity (e.g. Sokolova et al 2016;Wood et al 2016). Little, however, is known about their combined effects and our current understanding in filter feeders is limited to just a few studies where it has been shown that these factors influence the survival, energy metabolism and osmoregulatory capacity as well as weaken shells.…”
Section: Such Species Include Economically Important Filter Feeders Smentioning
confidence: 99%
“…The likely combined biological effects of this freshening with OA in the Baltic-Skagerrak System have received relatively little attention to date. Available data indicate increased sensitivity to OA in low-salinity populations (crustaceans, Gulf of Bothnia, Wood et al 2016 ), potential for freshening to counteract the positive effects of OA on reproductive success ( Fucus , Baltic, Serraõ et al Serrao et al 1999 ; Graiff et al 2017 ), and no substantive impacts of OA + freshening on microplankton community structure (Baltic Proper, Wulff et al 2018 ; Table 1 ). This important research area requires further experimental investigation before patterns in responses to this interaction can be identified.…”
Section: Interactive Effects Of Ocean Acidification: Species-level Rementioning
confidence: 99%
“…Finally, extant levels of adaptation to local conditions may mediate populations' sensitivity to future global change drivers (e.g. Lardies et al 2014;Wood et al 2016). For these reasons, the investigation of populations' and species' ability to mount plastic and adaptive responses to prevalent environmental changes is an absolute priority (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…; Wood et al. ). For these reasons, the investigation of populations’ and species’ ability to mount plastic and adaptive responses to prevalent environmental changes is an absolute priority (e.g.…”
mentioning
confidence: 97%